Defining diversity: a critical discourse analysis of public educational texts. Issue 1 (2nd January 2020) - Arce-Trigatti, Andrea; Anderson, Ashlee
ABSTRACT: With this paper we present findings from a cultural studies project that aims to illuminate and define the various, sometimes overlapping, conceptions of diversity in public educational discourses. We do so via a critical discourse analysis of select political texts: namely speeches by former Secretary of Education Arne Duncan that reference diversity as a focal point of intervention and reform (national and international in scope). We begin with a general overview of literature outlining diversity's historical links to the education sector, after which we describe our theoretical framework, data sources, and methodology. Next, we present the study's findings through the lens of two paramount themes: diversity as an economic input and diversity as a democratic input . To conclude, we provide discussions based on these findings, point to an overall lack of effort regarding the meaningful implementation of diversity policies, and suggest potential avenues for future research.